The safety of Lipistart, a medium-chain triglyceride based formula, in the dietary treatment of long-chain fatty acid disorders: a phase I study - MacDonald, Anita; Webster, Rachel; Whitlock, Matthew; Gerrard, Adam; Daly, Anne; Preece, Mary Anne; Evans, Sharon; Ashmore, Catherine; Chakrapani, Anupam; Vijay, Suresh; Santra, Saikat (Journal of Pediatric Endocrinology & Metabolism, 2018)
Children with long-chain fatty acid β-oxidation disorders (LCFAOD) presenting with clinical symptoms are treated with a specialist infant formula, with medium chain triglyceride (MCT) mainly replacing long chain triglyceride (LCT). It is essential that the safety and efficacy of any new specialist formula designed for LCFAOD be tested in infants and children. In an open-label, 21-day, phase I trial, we studied the safety of a new MCT-based formula (feed 1) in six well-controlled children (three male), aged 7-13 years (median 9 years) with LCFAOD (very long chain acyl CoA dehydrogenase deficiency [VLCADD], n=2; long chain 3-hydroxyacyl CoA dehydrogenase deficiency [LCHADD], n=2; carnitine acyl carnitine translocase deficiency [CACTD], n=2). Feed 1 (Lipistart; Vitaflo) contained 30% energy from MCT, 7.5% LCT and 3% linoleic acid and it was compared with a conventional MCT feed (Monogen; Nutricia) (feed 2) containing 17% energy from MCT, 3% LCT and 1.1% linoleic acid. Subjects consumed feed 2 for 7 days then feed 1 for 7 days and finally resumed feed 2 for 7 days. Vital signs, blood biochemistry, ECG, weight, height, food/feed intake and symptoms were monitored. Five subjects completed the study. Their median daily volume of both feeds was 720 mL (range 500-1900 mL/day). Feed 1 was associated with minimal changes in tolerance, free fatty acids (FFA), acylcarnitines, 3-hydroxybutyrate (3-HB), creatine kinase (CK), blood glucose, liver enzymes and no change in an electrocardiogram (ECG). No child complained of muscle pain or symptoms associated with LCFAOD on either feed. This is the first safety trial reported of an MCT formula specifically designed for infants and children with LCFAOD. In this short-term study, it appeared safe and well tolerated in this challenging group.